2007
DOI: 10.1074/mcp.m700086-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Sialiome Using Titanium Dioxide Chromatography and Mass Spectrometry

Abstract: Strategies for biomarker discovery increasingly focus on biofluid protein and peptide expression patterns. Posttranslational modifications contribute significantly to the pattern complexity and thereby increase the likelihood of obtaining specific biomarkers for diagnostics and disease monitoring. Glycosylation is a common post-translational modification that plays a role e.g. in cell adhesion and in cell-cell and receptor-ligand interactions. Abnormal protein glycosylation has important disease associations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
317
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(329 citation statements)
references
References 34 publications
9
317
0
3
Order By: Relevance
“…Dietary supplementation of sialic acid leads to increases in sialic acid-containing glycoproteins in the frontal cortex and is associated with faster learning and memory in piglets (8). The nervous system contains an abundant array of sialylated molecules and it is therefore not sur-prising that changes in the sialiome (the content of sialylated glycoproteins (9)) of a neuron can regulate activity. Removal of sialic acids from membrane proteins by NEU3 in primary neurons leads to actin depolymerization and axonal growth through TrkA-mediated signaling (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary supplementation of sialic acid leads to increases in sialic acid-containing glycoproteins in the frontal cortex and is associated with faster learning and memory in piglets (8). The nervous system contains an abundant array of sialylated molecules and it is therefore not sur-prising that changes in the sialiome (the content of sialylated glycoproteins (9)) of a neuron can regulate activity. Removal of sialic acids from membrane proteins by NEU3 in primary neurons leads to actin depolymerization and axonal growth through TrkA-mediated signaling (10).…”
mentioning
confidence: 99%
“…However, using this procedure resulted in significant co-enrichment of nonphosphorylated peptides. Later we demonstrated that TiO 2 was able to selectively purify phosphorylated peptides and sialic acid-containing N-glycopeptides (9,17) if peptide samples are loaded onto the TiO 2 resin in a buffer containing high organic solvent, very low pH and a multifunctional acid, such as 2,5-dihydroxybenzoic acid or glycolic acid.…”
mentioning
confidence: 99%
“…NPLC allows either direct enrichment of peptides modified by various N-linked glycan structures using a ZICா-HILIC column (23)(24)(25)(26)(27) or targeting sialylated glycopeptides using a titanium dioxide micro-column (28). However, NPLC is neither effective for enriching less hydrophilic glycopeptides, e.g.…”
mentioning
confidence: 99%
“…Glycopeptide enrichment under normal-phase LC (NPLC) conditions has been demonstrated using various hydrophilic media and different capture and elution conditions (23)(24)(25)(26)(27)(28). NPLC allows either direct enrichment of peptides modified by various N-linked glycan structures using a ZICா-HILIC column (23)(24)(25)(26)(27) or targeting sialylated glycopeptides using a titanium dioxide micro-column (28).…”
mentioning
confidence: 99%
“…Therefore, high efficient and specific enrichment procedure is imperative for large-scale glycoproteome analysis. Recently, various methods, including hydrophilic interaction liquid chromatography [5,6], lectinbased affinity chromatography [7][8][9], hydrazide chemistry [10] and TiO 2 [11,12], have been developed, and further used for the selective enrichment of glycoproteins/glycopeptides. Among above-mentioned methods, Hydrazide gel-based solid-phase extraction becomes a popular technique, mainly due to its high efficiency and excellent selectivity, and has been used for the analysis of N-glycoproteome in various biological samples [10,[13][14][15].…”
mentioning
confidence: 99%